Nalar Teosofis sebagai Basis Epistemologis Kajian Agama dan Pengetahuan - Syafaq, Hammis (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2013)
This article is an attempt to study the development of epistemology that combines religion and science reasoning in the form of ?theosophical sense?. The goal is to provide the opportunity for religious reason and philosophy of reason to move, to walk, to work according to their capacities and freely without having to specify the amount of the portion in between. But at some point, they interact and complement each other. This study is expected to resolve the problem of the conflict between religion?which is based on religious arguments?and knowledge?which is based on human reason?, because each can meet in a single point of wisdom (meeting between aspects of divinity and humanity). Therefore, it has a humanitarian dimension of religion, as well as the knowledge which has dimensions of divinity.